2018
DOI: 10.5624/isd.2018.48.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Oral carcinoma cuniculatum, an unacquainted variant of oral squamous cell carcinoma: A systematic review

Abstract: PurposeOral carcinoma cuniculatum is a rare well-differentiated variant of oral squamous cell carcinoma. The purpose was to systematically review its unique features to differentiate it from other variants as verrucous carcinoma, papillary squamous cell carcinoma and well-differentiated squamous cell carcinoma.Materials and MethodsA systematic review was performed using MEDLINE, Dentistry and Oral Sciences Source and PubMed databases and any existing articles related to the research subject missed in the searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 31 publications
3
60
1
2
Order By: Relevance
“…By contrast, CCu are well documented and are probably one of the “family” of papilloverrucous dysplasias and carcinomas that affect the oral cavity, albeit one with specific histopathological features. Patients with CCu are usually aged >60 years, but the mean age in the present series is higher than that reported in a recent review, 2 which also found a slight female preponderance (55.8%). There are 2 reported instances of CCu in children younger than 10 years.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…By contrast, CCu are well documented and are probably one of the “family” of papilloverrucous dysplasias and carcinomas that affect the oral cavity, albeit one with specific histopathological features. Patients with CCu are usually aged >60 years, but the mean age in the present series is higher than that reported in a recent review, 2 which also found a slight female preponderance (55.8%). There are 2 reported instances of CCu in children younger than 10 years.…”
Section: Discussioncontrasting
confidence: 75%
“…The vast majority of the other reported cases suggest that the jaws, and particularly the mandibular alveolus, is the most common site of oral CCu. While local destruction is a common feature, metastasis is unusual, and as 3 of the 4 metastases stated to have occurred by Farag et al 2 were reported by Sun et al, 5 this figure is also unreliable. The etiology is uncertain; >30% of patients are tobacco smokers or heavy consumers of alcohol, or both.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations